A revised classification of the Gelidiellaceae (Rhodophyta) with descriptions of three new genera: Huismaniella, Millerella and Perronella. Issue 5 (1st October 2016) - Boo, Ga Hun; Van Nguyen, Tu; Kim, Jung Yeon; Gall, Line Le; Rico, Jose Manuel; Bottalico, Antonella; Boo, Sung Min
Abstract: The agarophyte family Gelidiellaceae currently includes 26 species in two genera, Gelidiella and Parviphycus, but the generic status and species boundaries have not been fully explored. In order to resolve taxonomic issues in the family, we analyzed mitochondria‐encoded cox1 and plastid‐encoded rbcL and psaA genes from types and fresh collections including topotype material. The Gelidiellaceae was resolved with five distinct groups, interpreted here as representing five genera: (1) Gelidiella, including the type, (2) Huismaniella gen. nov., (3) Millerella gen. nov., (4) Parviphycus s.str. including the type, and (5) Perronella gen. nov. Gelidiella was recognized as including a new species, G. flabella, that is described for specimens from Madagascar. A new genus, Huismaniella, is described for the species previously known as Gelidiella ramellosa, characterized by lateral tetrasporangial branchlets inserted at right angles on erect axes and irregularly arranged tetrasporangia. Parviphycus includes P. adnatus which is characterized by simple thalli with tetrasporangial branchlets formed directly on prostate axes and holdfasts forming continuous fringes along the entire length of prostrate axes. The new genus Millerella is described to accommodate five species previously known as Gelidiella or Parviphycus, characterized by tetrasporangial sori formed on erect axes or branches and unicellular rhizoids forming irregular clumps along prostrate axes. Perronella gracilis gen. et sp. nov. is described for plants with terete axes, multifarious branching, and monosporangia formed on erect axes and branches. The implications for nomenclature, taxonomic revisions, and biogeography in the Gelidiellaceae are discussed.